Mobilizing Science for Climate Change, Agriculture and Food Security: Engaging the Southeast Asian Media - Navarro, Rex; Joven, B.; Cruz, A. (2015)
In the context of agriculture and food security, science innovations on mitigating and adapting to climate change are available, but these are not well shared with next users and end users (especially farmers) and the public due to inadequate coverage by the mainstream media, a powerful partner in communication and engagement. The urgent need for media practitioners to have an accurate, science-based understanding of climate change and enhance their skills on environmental reporting gave CCAFS-SEA the impetus to conduct a series of inter-Center media seminar-workshops for key Southeast Asian media practitioners in collaboration with NARS and national media partners. Overall, the media seminar-workshop series was participated in by 149 media professionals and 39 government information officers in SEA. The journalists came from print, broadcast (radio-TV) and web-based media outlets. This initiative was a critical first step in implementing CCAFS-SEA’s regional engagement and communication plan, pursued as a CGIAR inter-Center activity in collaboration with NARS and national media partners. The content of the two-day seminar-workshops focused on two major areas: science innovations in climate change, agriculture and food security and communicating climate change. Complementing the plenary sessions was a story ideas marketplace which primarily served as a venue for dialogue among participants and resource persons on possible stories to be developed and released in their respective media outlets. A half-day field tour exposed participants to climate change and agriculture R4D either by a CGIAR Center or a NARS partner and/or climate smart agriculture practices of a farming community. One of the outcomes of the SEA media workshop series in the Philippines is the forging of partnership with a private company, Metro-Pacific Investments Corporation (MPIC), which provided volunteer funding a proposal of the Philippine Agriculture Journalists, Inc. and the Department of Agriculture (DA) to replicate the initiative in strategic regions in the Philippines. This is an unprecedented public-private-civil society partnership in communicating climate change, agriculture and food security in the Philippines. With six media seminar-workshops completed in Cambodia, Lao PDR, Vietnam and the Philippines, the next step for CCAFS-SEA would be to move the engagement process further with partners in the region.